El uso del aprendizaje basado en proyectos para fomentar las habilidades orales en inglés en escuelas rurales multinivel en Saboyá, Boyacá (2023)
This research project aims to illustrate and address the challenges of teaching a second language in three different rural sites of the I.E. Escuela Normal Superior de Saboyá, located in Boyacá, Colombia. The study consisted of implementing project-based learning, an approach in which students were encouraged to learn English through the creation of a collaborative project along the course, within the educational context of multilevel schools, where students learned autonomously, making it meaningful for their cognitive and social development. The instruments to collect information comprised the students’ portfolios, video recordings, and pre-service teachers’ reflective journals. The results demonstrated that it was the first time that the students were exposed to this learning methodology while learning English, which positively impacted their interest in learning and using a second language. Overall, the students boosted their use of English in the classroom thanks to the use of PBL, feeling more involved in interacting and communicating in the target language.